Konsep Human Interest Pada Festival Musik “The Sounds Project” Menarik Minat Kaum Muda - Rizky, Ramadhanty Cahyaning (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
A music festival is a series of music events featuring many performers and more than one stage. The Sound Project (TSP) Music Festival is one of the choices of music festivals for young people. Through the concept of human interest photos uploaded to the Instagram account @thesoundsproject, it becomes an interesting event to invite young people to come to The Sounds Project. This study aims to determine the concept of human interest photos in attracting young people to visit The Sounds Project Music Festival 2023 through the role of Instagram social media and increasing TSP awareness. A qualitative approach was used in this study by conducting in-depth interviews and data collection. The results of this study indicate that utilizing the concept of human interest can attract young people's interest in The Sound Project music festival so that it can increase awareness of the music festival through Instagram social media @thesoundsproject. This study can be a reference for The Sound Project to increase the use of social media, not only by using the concept of human interest but also using methods that can make content more interactive.